Diversas enfermedades bacterianas - Schwartz, Howard F. (International Center for Tropical Agriculture, 1980)
Among the bacterial diseases that attack beans are (1) halo blight (Pseudomonas phaseolicola), which is distributed worldwide and survives in infected seeds and blunt residue. Three to five days after infection, water-soaked spots appear on the lower leaf surface, stem and pods; (2) bacterial wilt (Corynebacterium flaccumfaciens) has been registered in the USA, but its existence in L.A. is unknown. Drought and temp more than 32 degrees Celsius are favorable conditions for disease development The bacterium infects plants through the seed and wounds on aerial plant organs and roots; (3) bacterial brown spot (Pseudomonas syringae) produces flecks or necrotic brown lesions on the stem and pods. The bacterium has a wide host range. For efficient disease control, deep plowing, crop rotation and the use of disease-free seeds, adequate chemical products and resistant var. are recommended. The symptoms and damage caused by the disease are illustrated in color. (CIAT)